Hasil Belajar Siswa: Tinjauan Atas Regulasi Belajar, Disiplin Belajar, Lingkungan Sekolah, dan Persepsi Dukungan Guru - Didit Darmawan; Mohammad Fasikhul Lisan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This literature study aims to analyze the interaction between self-regulated learning, learning discipline, school environment, and students' perceptions of teacher support in determining learning outcomes. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that self-regulated learning provides direction and strategies, while learning discipline supplies consistency and persistence in executing those strategies. Their interaction creates a positive cycle where good planning combined with discipline produces successful experiences that reinforce self-efficacy and motivation. A conducive school environment, both physically and socially, provides a safe and stimulating arena for developing student capacities. Students' perceptions of teacher support, encompassing emotional, instrumental, informational, and appraisal dimensions, become the key determinant of whether students will fully utilize available resources in the school environment. These four variables theoretically demonstrate significant contributions to students' academic achievement. The synergy between internal and external factors forms an educational ecosystem that empowers students to reach their optimal potential. This study contributes theoretically to enriching the ecological perspective on educational psychology and practically provides reflective foundations for teachers, principals, and policymakers in optimizing both internal and external factors that shape learning outcomes